Evaluation of gemcitabine efficacy after the FOLFIRINOX regimen in patients with advanced pancreatic adenocarcinoma. Issue 16 (April 2017) - Gilabert, Marine; Chanez, Brice; Rho, Young Soo; Giovanini, Marc; Turrini, Olivier; Batist, Gerald; Kavan, Petr; Raoul, Jean Luc
Abstract : Abstract: To evaluate gemcitabine efficacy in advanced pancreatic cancer patients after the FOLFIRINOX regimen. Patients with locally-advanced or metastatic pancreatic adenocarcinoma from French and Canadian centers, who were treated with the first-line FOLFIRINOX regimen (FFX L1), followed by gemcitabine monotherapy as a second-line treatment (GEM L2), were retrospectively evaluated. Statistical analyses were performed on the demographic, toxicity, and response rate data. Overall survival (OS) and progression-free survival (PFS) were assessed using the Kaplan–Meier method. Seventy-two patients were reviewed (median age of 63.5 years [range, 32–75 years], men [62%], predominantly pancreatic head tumor location [51%] and metastatic disease [64%] at the time of diagnosis). The objective response rate to GEM-L2 treatment was 8/72 (11%), and 32 patients (44%) experienced a clinical benefit from gemcitabine. Four patients had a partial response to GEM-L2, although they previously showed a progressive response following FFX-L1 treatment. The median OS for the entire cohort was 13.6 months (95% confidence interval [CI]: 2.0–35). The median PFS of the GEM-L2 group was 2.5 months (95% CI: 0.2–10.8) with no statistical differences between patients with controlled or progressive disease on FFX-L1 therapy. Gemcitabine as a second-line treatment for advanced pancreatic adenocarcinoma after FOLFIRINOX failure showed clinical benefits in some patients.